ETNISITAS DAN POLITIK LOKAL PROVINSI LAMPUNG (Study Kasus Etnisitas pada Pemilukada Lampung Selatan 2010) - Dega Okta Munaleza; Susilo Utomo; Fitriyah . (Journal of Politic and Government Studies, 2014)
In the political arena in the district / city , competition between local and ethnic immigrants looks verystrong . Regional Head Election ( Election ) June 30, 2010 , held simultaneously in five districts / cities inLampung has prove it . The combination of Java and Lampung ethnic almost always arise until thegeopolitical characteristics of an area in Lampung could be represented on the winner of Regional HeadElection . In Metro Citie majority ethnic Javanese , for example , Lukman Hakim and Saleh Chandra Javabloody win the General Election . In Pesawaran district the ethnic composition was balanced betweenLampung and Java , the winner is Aries Password ( Lampung ) and Musiran ( Java ) . The same case is seenin East Lampung , although with suspect status , Satono , was dominate sound among 60 percents in themiddle of Java bloody . In South Lampung regency with dominant Lampung ethnic composition thanJavanese , so winning the Regents and Vice Regents elected, they are Waki Rycko Menoza SZP - EkiSetyanto . The purpose of this study is to determine " the role of ethnicity in the general election in SouthLampung regency at 2010”. The research methods are qualitative - descriptive type because descriptivestudies systematically describe a situation , problem , phenomenon , service or program , the provision ofinformation about a situation , problem , social life , or describe the attitude of the people responding to aparticular issue. The study shows a year before the General Election held in South Lampung regency ,political dynamics nomination process Regent and Vice Regent South Lampung regency preceded theexistence of rumors in the community about the pair potential between the " sons of ethnic " with " settlers " .The issue of ethnicity appears seven pairs of candidates Regent and Vice Regent South Lampung , the wholefamily tries to accommodate the heterogeneity of ethnic groups in South Lampung . Number 1 ( one ) ; H.Rycko Menoza , SE , SH , . MBA ( ethnic Lampung ) and H. Eky Setyanto ( Javanese ) won the SouthLampung Election at 2010. Theoretically ethnicity can be a serious issue in the election , but in SouthLampung at 2010, the issue of ethnicity could not be negative or even conflict access , so until the vote countends, it can take place smoothly and without significant disruption . The efforts of politicization of ethnicityin South Lampung Election can be clearly addressed by the community. Potential force of Rycko - Eky is inthe socio antrpologis adequate approach, which is combined synergistically and regardless of bad sounds tothis couple . Integrative and egalitarian approach undertaken by the couple is able to reach people's heartsas both are popular figure in the people of South , and is known to have positive social attitudes , as well asrepresenting the interests of ethnic Lampung and Java , as the majority of the population of South Lampungregency .Keywords: Ethnic, Regional Head Election, South Lampung regency